Sleep medicine for dentists a practical overview. - Lavigne, Gilles J.; Cistulli, Peter A .; Smith, Michael T. (Hanover Park, IL : Quintessence Publishing Co, Inc., 2019)
This concise clinical handbook educates dental practitioners seeking to understand, recognize, and manage disorders such as sleep apnea, sleep bruxism, and chronic pain, which often interfere with or intrude into sleep and are critically important to the practice of dentistry. Leading experts in medicine and dentistry articulate and guide readers in performing the specific responsibilities of dental practitioners, such as routinely examining patients for the risk of sleep-disordered breathing; providing guidance and appropriate referrals to patients who report snoring, sleepiness, and morning headache; managing the tooth damage or pain generated by bruxism; knowing when to prescribe oral appliances and understanding their associated risks; and collaborating closely with maxillofacial surgeons or ENT specialists when surgery is indicated. This unique book is a rapid source of practical information for students, practicing dentists, and researchers who wish to expand their knowledge base on this important topic.
Sleep medicine for dentists : a practical overview -- Table of contents -- foreword -- preface -- contributors -- Section I. INTRODUCTIONTO DENTAL SLEEP MEDICINE -- CHAPTER 1: THE NATURE OF SLEEP -- CHAPTER 2: SLEEP NEUROBIOLOGY -- CHAPTER 3: CLASSIFICATION OF SLEEP DISORDERS -- SECTION II: SLEEP BREATHING DISORDERS -- CHAPTER 4: SLEEP-RELATED BREATHING DISORDERS -- CHAPTER 5: PATHOPHYSIOLOGY OF OBSTRUCTIVE SLEEP APNEA -- CHAPTER 6: LONG-TERM CONSEQUENCES OF OBSTRUCTIVE SLEEP APNEA -- CHAPTER 7: CLINICAL APPROACH TO DIAGNOSIS OF OBSTRUCTIVE SLEEP APNEA -- CHAPTER 8: UPPER AIRWAY IMAGING IN OBSTRUCTIVE SLEEP APNEA -- CHAPTER 9: AN OVERVIEW OF OBSTRUCTIVE SLEEP APNEA TREATMENT -- CHAPTER 10: ORAL APPLIANCES -- CHAPTER 11: DENTOFACIAL ORTHOPEDICS -- SECTION III: SLEEP BRUXISM AND MOVEMENT DISORDERS -- CHAPTER 12: DEFINITIONS, EPIDEMIOLOGY, ANDETIOLOGY OF SLEEP BRUXISM -- CHAPTER 13: OROFACIAL MOVEMENT DISORDERS IN SLEEP -- CHAPTER 14: CLINICAL APPROACH TO DIAGNOSIS OF SLEEP BRUXISM -- CHAPTER 15: PATHOPHYSIOLOGY OF SLEEP BRUXISM -- CHAPTER 16: SLEEP BRUXISM IN CHILDREN -- CHAPTER 17: MANAGEMENT OF SLEEP BRUXISM -- SECTION IV: SLEEP AND OROFACIAL PAINS -- CHAPTER 18: PATHOPHYSIOLOGIC CONCEPTUALIZATIONS OF CHRONIC PAIN -- CHAPTER 19: MECHANISMS OF SLEEP LOSS-PAIN INTERACTIONS -- CHAPTER 20: CLINICAL IMPLICATIONS OF SLEEPLOSS-PAIN INTERACTIONS -- CHAPTER 21: ASSOCIATION OF OROFACIAL PAIN CONDITIONS AND SLEEP DISTURBANCE -- CHAPTER 22: IMPACT OF COMMON TEMPOROMANDIBULAR DISORDER COMORBIDITIES ON SLEEP QUALITY AND OROFACIAL PAIN -- CHAPTER 23: PHARMACOLOGIC MANAGEMENT OF SLEEP-PAIN INTERACTIONS -- CHAPTER 24: NONPHARMACOLOGIC MANAGEMENT OF INSOMNIA AND PAIN -- Conclusion -- Index.
Includes bibliographical references and index.
Keywords: Sleep Disorders -- diagnosis; Tooth Diseases -- complications